Development of robotic arm system replica to assist seeding in agriculture / Muhammad Faris Khalid - Khalid, Muhammad Faris (2024)
This study focuses on the application of robotic technology in agriculture to address the challenges of sustainability, productivity, and the increasing demands of food production in a rapidly changing world. The manual method of seeding in agriculture is time-consuming and lacks accuracy. To overcome these limitations, the study develops an accurate robotic arm system replica using an Arduino mechanical robotic arm. The primary objective is to design a system replica capable reduce the time of completing the seeding process. The system replica's performance is then evaluated based on time and accuracy. It is anticipated that this system replica will outperform human capabilities in terms of speed and accuracy. Integrating robotic technology into agriculture enhances the potential for a more sustainable and productive farming industry, enabling it to meet the evolving global food production needs.